A Method for the Appraisal of Natural Values Serving the Preparation of a Landscape Audit: A Case Study from Poland - Anna Mazur; Krystyna Kurowska (Resources, 2024)
The article focuses on the development of a universal method for the appraisal of values of a natural landscape in administrative division units. The Dobre Miasto municipality serves as a case study. The municipality lies in the heart of Warmia, a region with centuries-long historical tradition. This paper also mentions solutions adopted in Poland in the consequence of the ratification of the European Landscape Convention. Following many years of research, changes in the natural landscape and directions in the measures taken to protect it were traced. In the face of current transformations in space, efforts to protect and conserve natural wealth are difficult. Compromises are unavoidable for the sake of saving the region’s valuable natural assets while allowing its development. The aim of this study was to identify the natural values in the chosen research area, and to develop a method for their appraisal. The identification of the natural elements deserving protection substantiated rational location decisions in space. This is particularly important in the case of a natural landscape, which is difficult to evaluate and whose estimated value is often a result of a subjective assessment. The valorisation of the natural landscape in the chosen municipality allowed us to identify new areas, which at present are outside the boundaries of legally protected areas but which deserve protection owing to their highly valuable natural properties. The proposed method for the appraisal of natural values can be used in shaping a spatial policy, in spatial planning and development, and, above all, in the preparation of landscape audits. The proposed method fills the gap in the legal regulations adopted in Poland in the field of strengthening the protection of natural and cultural values since no comprehensive guidelines for the evaluation of landscape attributes for the purposes of landscape protection and development have been elaborated thus far.